Register Variation and Style Shifting in Sociolinguistics - Baxtiyorova Lola Otabekovna (Academia One, 2025)
This article explores the concepts of register variation and style shifting within the field of sociolinguistics. It examines how language changes depending on the audience, setting, and purpose of communication (register variation), as well as how individuals adjust their language style based on social identity, power dynamics, and group affiliation (style shifting). The article also highlights the connection between these two concepts, demonstrating how language is a dynamic and adaptable tool that reflects both the social context and personal identity. Examples from multilingual communities and various social interactions are used to illustrate these phenomena, emphasizing the fluidity of language in response to different social factors.
Keywords: sociolinguistics; register variation; style shifting